Plant Extracts of the Family Lauraceae: A Potential Resource for Chemopreventive Agents that Activate the Nuclear Factor-Erythroid 2-Related Factor 2/Antioxidant Response Element Pathway - Shen, Tao; Chen, Xue-Mei; Harder, Bryan; Long, Min; Wang, Xiao-Ning; Lou, Hong-Xiang; Wondrak, Georg T.; Ren, Dong-Mei; Zhang, Donna D. (Planta Medica, 2014)
Cells and tissues counteract insults from exogenous or endogenous carcinogens through the expression of genes encoding antioxidants and phase II detoxifying enzymes regulated by antioxidant response element promoter regions. Nuclear factor-erythroid 2-related factor 2 plays a key role in regulating the antioxidant response elements-target gene expression. Hence, the Nrf2/ARE pathway represents a vital cellular defense mechanism against damage caused by oxidative stress and xenobiotics, and is recognized as a potential molecular target for discovering chemopreventive agents. Using a stable antioxidant response element luciferase reporter cell line derived from human breast cancer MDA-MB-231 cells combined with a 96-well high-throughput screening system, we have identified a series of plant extracts from the family Lauraceae that harbor Nrf2-inducing effects. These extracts, including Litsea garrettii (ZK-08), Cinnamomum chartophyllum (ZK-02), C. mollifolium (ZK-04), C. camphora var. linaloolifera (ZK-05), and C. burmannii (ZK-10), promoted nuclear translocation of Nrf2, enhanced protein expression of Nrf2 and its target genes, and augmented intracellular glutathione levels. Cytoprotective activity of these extracts against two electrophilic toxicants, sodium arsenite and H2O2, was investigated. Treatment of human bronchial epithelial cells with extracts of ZK-02, ZK-05, and ZK-10 significantly improved cell survival in response to sodium arsenite and H2O2, while ZK-08 showed a protective effect against only H2O2. Importantly, their protective effects against insults from both sodium arsenite and H2O2 were Nrf2-dependent. Therefore, our data provide evidence that the selected plants from the family Lauraceae are potential sources for chemopreventive agents targeting the Nrf2/ARE pathway.
Keywords: Lauraceae; Cinnamomum; Litsea; plant extracts; Nrf2/ARE pathway; chemoprevention